Bi Dots Confined by Functional Carbon as High‐Performance Anode for Lithium Ion Batteries. (14th April 2020) - Hong, Wanwan; Wang, Anni; Li, Lin; Qiu, Tianyun; Li, Jiayang; Jiang, Yunling; Zou, Guoqiang; Peng, Hongjian; Hou, Hongshuai; Ji, Xiaobo
Abstract: Fabrication of Bi/C composites is a common approach to alleviate the severe volume expansion of Bi alloy‐based anodes with a high theoretical capacity of 3800 mAh cm −3 for lithium ion batteries (LIBs). However, the complicated and tedious synthetic routes restrict its large‐scale preparation and practical applications. Herein, a spongiform porous Bi/C composite (marked as Bi@PC) through the carbothermal reduction (CTR) method is constructed. Bi nanodots are in situ confined in a porous carbon substrate activated by the gases produced from the decomposition of the sodium phytate precursor, indicating the feasibility and simplicity of this route. In charge/discharge processes, Bi nanodots embedded in carbon matrix are effective enough to accommodate the strain change and shorten the migration distance. In addition, the porous carbon forms an efficient conductive network for electron shutting. When utilized for lithium storage, a superb capacity of 520 mAh g −1 at 0.2 A g −1 after 100 cycles and a satisfying long cyclic stability of 380 mAh g −1 at 0.5 A g −1 after 500 cycles are achieved. The excellent Li‐storage performance and this handy preparation method jointly make this Bi/C composite a potential anode for LIBs, and could inspire the preparation of other alloy‐type anodes. Abstract : Complicated and tedious synthetic routes always restrict the large‐scale preparation and application of Bi/C anode materials for lithium ion batteries. Herein, a spongiform porous Bi/C composite is constructed through a one‐step carbothermal reduction method, which presents a superb cyclic stability of 380 mAh g −1 at 0.5 A g −1 after 500 cycles.